Gut microbiota alterations in golden snub-nosed monkeys during food shortage and parturition-nursing periods - Lan, Guanwei; Ma, Rui; Zhou, Yanshan; Lu, Zhantao; Zhu, Biqing; Liu, Juan; Wu, Wei; Zhang, Yue; Liu, Jiabin; Gu, Haijun; Lin, Jie; Wei, Wei; et al. (Frontiers in Microbiology, 2025)
Adopting unique survival strategies during spring food shortages and simultaneous parturition and nursing is crucial for golden snub-nosed monkeys. Social behaviors, such as altruism within one-male units (OMUs), are decisive for family health, but the role of microbiota in regulating these behaviors remains unknown. We conducted the gut microbiota from members of 10 OMUs using 16S RNA sequencing technology. We found that in adult males, gut microbiota diversity significantly decreased in food shortages and parturition-nursing period. Meanwhile, there was a notable reduction in 12 metabolism-related pathways, including those related to carbohydrates, amino acids, and lipid. The gut microbiota of adult male monkeys shifts from being enriched with the genera Akkermansia in winter to the genera norank Muribaculaceae in spring. This transition alters the pathways for nutrient acquisition, thereby reducing the consumption of stored energy. In contrast, other OMU members (adult females and subadults) did not experience adverse effects on the metabolic functions of their gut microbiota during the food-scarce spring, which is also a critical period for parturition and lactation in adult females. This study elucidates the co-evolution of altruistic behavior and gut microbiota in Sichuan snub-nosed monkeys, insights into the interaction mechanisms between mammalian microbiota and survival strategies.